1976
DOI: 10.1111/j.1423-0410.1976.tb02811.x
|View full text |Cite
|
Sign up to set email alerts
|

Familial Clustering of Selective IgA Deficiency

Abstract: Serum IgA levels of 35 healthy IgA-deficient index cases, of their 180 first-degree relatives, and of 31 other family members were studied. IgA deficiency was detected in 7.2% of the first-degree relatives, which is significantly more than the 0.25% frequency of IgA deficiency in healthy Finnish blood donors. Subnormal serum IgA levels were found in additional 13 (7.2%) first-degree relatives. The familial clustering of IgA deficiency seemed to be controlled by multigenic factors. IgA-deficient persons and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 17 publications
3
25
0
1
Order By: Relevance
“…Many multicase families show a dominant transmission of the disorder, whereas in other families, it follows autosomal recessive inheritance. 6,7 No primary genetic factor has been identified and variation in familial inheritance patterns suggests that IgAD may be due to multiple genetic defects. Several studies have shown association of HLA alleles with IgAD, [8][9][10][11] and the extended haplotype HLA-A1-B8-DR3 occurs more frequently in individuals with IgAD than it does in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Many multicase families show a dominant transmission of the disorder, whereas in other families, it follows autosomal recessive inheritance. 6,7 No primary genetic factor has been identified and variation in familial inheritance patterns suggests that IgAD may be due to multiple genetic defects. Several studies have shown association of HLA alleles with IgAD, [8][9][10][11] and the extended haplotype HLA-A1-B8-DR3 occurs more frequently in individuals with IgAD than it does in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Oligonucleotide primers and PCR conditions, Mg 2ϩ concentrations, and annealing temperatures are shown as supplemental information or were reported previously (27,28). 4 Allelic sizes, numbers and their frequencies, observed heterozygosity, and polymorphism information content are shown as supplementary information. 4 In addition, genotypes at three cSNPs in the BTLNL2 gene (939A3 G, 1050G3 A, and 1078A3 G), located ϳ20 kb centromeric of LH1 ( Fig.…”
Section: Marker Loci and Genotypingmentioning
confidence: 99%
“…4 Allelic sizes, numbers and their frequencies, observed heterozygosity, and polymorphism information content are shown as supplementary information. 4 In addition, genotypes at three cSNPs in the BTLNL2 gene (939A3 G, 1050G3 A, and 1078A3 G), located ϳ20 kb centromeric of LH1 ( Fig. 1) (29), were determined using nucleotide sequencing with BigDye terminators (Applera, Norwalk, CT) as described (26) to establish a telomeric limit of the candidate region on a subset of haplotypes.…”
Section: Marker Loci and Genotypingmentioning
confidence: 99%
See 2 more Smart Citations